Evaluation of copper and zinc concentrations in dried fruits collected from marketplaces of Peninsular Malaysia: health risk assessment, food security implications, and the necessity for regular monitoring - Yap, C. K.; Al-Mutairi, K. A. (Corvinus University of Budapest, 2025)
This study investigates the concentrations of Copper (Cu) and Zinc (Zn) in five types of dried fruits (raisins, kiwis, dates, figs, and apricots) collected from marketplaces in Peninsular Malaysia, while assessing their potential health risks based on the maximum permissible limits (MPLs) set by Malaysian Food Regulations (1985). After converting from the dry weight basis, the results show that figs exhibited the highest levels of Cu (9 mg/kg wet weight) and Zn (9.95 mg/kg wet weight), while kiwis had the lowest concentrations for both metals. Estimated daily intake (EDI) and target hazard quotient (THQ) values were calculated for each metal, revealing low health risks, with THQs for all fruits remaining below 1. Figs had the highest THQs for Cu (0.61) and Zn (0.08), suggesting moderate caution in frequent consumption. The study also emphasizes the importance of regularly monitoring metal concentrations in dried fruits, improved agricultural and post-harvest practices, and the need for clear labelling to inform consumers about potential metal content. These findings provide critical insights into ensuring food safety, reducing metal exposure, and promoting dietary diversity for better public health outcomes.